Rappaport’s triads - Kapustin, Petr (project baikal, 2025)
The article presents history and description of the triadic system of vision organization. The author emphasizes the importance of the triad principle for Rappaport’s thinking. He characterizes the triads in his theory of architecture.
Keywords: Vitruvius; triadic thinking; ontology; phenomenology; environment; norm